The “Motor of the Day”: Parent and School-Age Children’s Cognitions, Barriers, and Supports for Breakfast - Eck, Kaitlyn M. (Int J Environ Res Public Health, 2019)
Despite the many benefits of regular breakfast consumption few parents and children consume this meal every day and research examining the determinants of breakfast consumption is limited. Thus, the purpose of this study was to examine breakfast-related cognitions (i.e., beliefs, attitudes, facilitators, barriers) of parents and school-age children (ages 6–11 years) using the constructs of Social Cognitive Theory as a guide. Parents (n = 37) and children (n = 41) participated in focus group discussions held in community settings in 3 states (FL, NJ, WV). Data were qualitatively content analyzed to detect trends. Parents felt breakfast was important for numerous reasons. Parents expressed concern about the healthfulness of some traditional breakfast options, preferring breakfasts containing mostly fruits, vegetables, and protein and fewer carbohydrates. Parents identified lack of time as the greatest barrier to breakfast consumption. To overcome this barrier, they utilized grab-and-go foods, prepared breakfast ahead of time, and got up earlier. Utilizing the school breakfast program was another strategy mentioned, however some were concerned about the nutritional quality of this option. Children recognized the importance of breakfast and cited several benefits. The greatest barrier to breakfast identified by children was feeling rushed in the morning. To overcome barriers, children suggested having a morning routine, selecting or preparing breakfast foods ahead, and relying on parents to encourage breakfast consumption. The effectiveness of interventions aiming to improve breakfast intake may be improved by addressing parent and child breakfast-related cognitions and tailoring interventions to address their needs.